Kajian Sosio-Historis Pendidikan Islam Indonesia Era Reformasi - Afiful Ikhwan (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
The reform era was born as a correction, improvement, and refinement of various weaknesses of previous government policies. The government of the reform era has also integrated religious education into the national education system, in terms of law or legislation, budget, human resources, and so forth. Strategies that need to be declared to improve future Islamic education are socio-political strategies, cultural strategies, and sociocultural strategies.